AIChE equipment testing procedure. a guide to performance evaluation and site testing analysis (AIChE equipment testing procedure., 2013)
This book provides chemical engineers and plant managers with helpful advice to assess and measure the performance of centrifugal compressors. From petrochemical refining and natural gas production to air separation plants, efficient, safe, and environmentally-sound operations depend on reliable performance by centrifugal compressors. Topics include: a step-by-step approach to preparing for, planning, executing, and analyzing tests of centrifugal compressors, with an emphasis on methods that can be conducted on-site--and with an acknowledgement of the strengths and limitations of these methods; definitions of relevant terms; a selection of instrumentation and identification of elements to be measured; strategies for data collection and evaluation; recommendations for when to schedule testing; as well as computation and interpretation of results, including guidelines for field modifications and analysis of results. --